Respuesta :

1.

Looks like

[tex]y=2\sqrt[3]{x}+\dfrac1{x^2}+\pi[/tex]

Write [tex]\sqrt[3]{x}[/tex] as a fractional power, [tex]x^{1/3}[/tex]. This makes it more obvious that the power rule should be used here.

[tex]y'=(2x^{1/3})'+(x^{-2})'+\pi'[/tex]

[tex]y'=\dfrac23x^{-2/3}-2x^{-3}[/tex]

[tex]y'=\dfrac2{3\sqrt[3]{x^2}}-\dfrac2{x^3}[/tex]

2.

[tex]y=(\sin(2x)+\tan(3x))^e[/tex]

Power and chain rule:

[tex]y'=\left((\sin(2x)+\tan(3x))^e\right)'[/tex]

[tex]y'=e(\sin(2x)+\tan(3x))^{e-1}(\sin(2x)+\tan(3x))'[/tex]

[tex]y'=e(\sin(2x)+\tan(3x))^{e-1}(\cos(2x)(2x)'+\sec^2(3x)(3x)')[/tex]

[tex]y'=e(\sin(2x)+\tan(3x))^{e-1}(2\cos(2x)+3\sec^2(3x))[/tex]

ACCESS MORE